One-electron oxidation of antioxidants: A kinetic-thermodynamic correlation - Villata, Laura S. (2013)
The values of the bimolecular rate constants for the reactions of 2,2′-azino-bis(3-ethylbenz-thiazoline-6-sulfonic acid) radical cation with epicatechin (((2.4±0.2)) s−1 M−1), and epigallocatechingallate ((29±5) s−1 M−1) were obtained by spectrophotometric measurements. We propose a correlation between the Gibbs energy ΔGo for the one-electron charge-transfer reactions from several antioxidants to radical species and the rate constants of the corresponding bimolecular reactions. This correlation can be used to predict rate constants of reactions of known ΔGo values.